Dictating High‐Capacity Lithium–Sulfur Batteries through Redox‐Mediated Lithium Sulfide Growth. Issue 6 (7th June 2019) - Zhao, Meng; Peng, Hong‐Jie; Wei, Jun‐Yu; Huang, Jia‐Qi; Li, Bo‐Quan; Yuan, Hong; Zhang, Qiang
Abstract: Regulating the solid product growth is critical for achieving high capacities in rechargeable batteries based upon multiphase and multielectron dissolution–precipitation chemistries (e.g., lithium–sulfur chemistry). The intrinsic redox mediators, polysulfides, are insufficient for effective regulation due to the dynamically changed species and concentration. Herein cobaltocene (CoCp2 ) is introduced as a persistent extrinsic redox mediator to dictate an alternative growing pathway toward three‐dimensional lithium sulfide growth, which enables at most 8.1 times enhancement in discharge capacities at harsh conditions of high‐rate (>1 C) or electrolyte‐lean operation (electrolyte/sulfur ratio of 4.7 µL mgS −1 ). The faster kinetics and higher diffusivity of CoCp2 play an essential role in regulating lithium sulfide growth and increasing discharge capacities. This work not only illustrates an effective strategy to increase the capacity of high‐rate or electrolyte‐lean lithium–sulfur batteries but also paves a way toward the rational design of novel redox mediators for dissolution–precipitation energy chemistries. Abstract : The cobaltocene redox mediator is found to dictate an alternative growing pathway toward three‐dimensional lithium sulfide growth, which enabled at most 8.1 times enhancement in discharge capacities at harsh conditions of high‐rate or electrolyte‐lean operation. This work also paves a way toward the rational design of novel redox mediators for dissolution–precipitation energy chemistries.